Atrial Fibrillation After Patent Foramen Ovale Closure: Incidence, Pathophysiology, and Management - Anastasios Apostolos; Dimitrios Tsiachris; Maria Drakopoulou; Georgios Trantalis; Georgios Oikonomou; Nikolaos Ktenopoulos; Chrysavgi Simopoulou; Odysseas Katsaros; Sotirios Tsalamandris; Constantina Aggeli; Georgios Tsivgoulis; Costas Tsioufis; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
This comprehensive review explores the incidence, pathophysiology, and management of atrial fibrillation (AF) following percutaneous closure of patent foramen ovale (PFO). Although AF is considered a common adverse event post PFO closure, its incidence, estimated at <5%, varies based on monitoring methods. The review delves into the challenging task of precisely estimating AF incidence, given subclinical AF and diverse diagnostic approaches. Notably, a temporal pattern emerges, with peak incidence around the 14th day after closure and a subsequent decline after the 45th day, mimicking general population AF trends. The pathophysiological mechanisms behind post PFO closure AF remain elusive, with proposed factors including local irritation, device‐related interference, tissue stretch, and nickel hypersensitivity. Management considerations encompass rhythm control, with flecainide showing promise, and anticoagulation tailored to individual risk profiles. The authors advocate for a personalized approach, weighing factors like age, comorbidities, and device characteristics. Notably, postclosure AF is generally considered benign, often resolving spontaneously within 45 days, minimizing thromboembolic risks. Further studies are required to refine understanding and provide evidence‐based guidelines.